Streptococcus plurianimalium peritonitis in a patient on continuous ambulatory peritoneal dialysis: a case report - Arimuthu, Durga Arinandini; Lim, Christopher Thiam Seong (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Streptoccoccus plurianimalium is a rare pathogen that has recently made a crossover from its common host, animals to humans. As reports start to emerge from this pathogen, it has come to light that it can cause clinically significant infections in a broad spectrum of systems. However, the mode of transmission of this pathogen has not yet been fully established. We report here a case of Streptoccoccus plurianimalium peritonitis in a patient undergoing continuous ambulatory peritoneal dialysis in our centre. To the best of our knowledge, this is the first case report of a Streptoccoccus plurianimalium peritonitis in an end-stage kidney disease patient.